Dietary and Plasma Carotenoids Are Positively Associated with Alpha Diversity in the Fecal Microbiota of Pregnant Women: The PEAPOD Pilot Study (FS06-08-19). (13th June 2019) - Comstock, Sarah; Sugino, Kameron; Vevang, Karin; Peterson, Lisa; Koratkar, Revati; Gross, Myron; Kerve, Jean
Abstract: Objectives: Determine associations among reported carotenoid intake, plasma carotenoid levels, and fecal bacterial communities in pregnant women. Methods: Pregnant women ( n = 27) were enrolled in a 2-arm, randomized, controlled, feasibility trial of a diet intervention during late pregnancy. Results presented are cross-sectional from one study visit combined across both study arms. Plasma samples were collected at the 36 week prenatal clinic visit. Fecal samples were self-collected and returned in ∼1 wk along with self-administered surveys including a dietary checklist ( n = 25) reflective of dietary intake over the past 24 hr. Plasma carotenoids were analyzed by HPLC with UV. Fecal bacteria were analyzed by 16S rRNA DNA (v4 region) sequencing. Reported results are from 23 women with complete data. Results: Recent intake included: carrots, sweet potatoes, mangos, apricots, and/or bell peppers for 48% of women; oranges/orange juice (17%); egg (39%); tomato/tomato-based sauces (52%); fruits (83%); vegetables (65%). Average plasma levels were 6.4 ug/dL α-carotene (AC), 17.7 ug/dL β-carotene (BC), 11.4 ug/dL cryptoxanthin (CR), 39.0 ug/dL trans-lycopene (TL), and 29.8 ug/dL zeaxanthin and lutein (ZL). AC and BC levels were higher in pregnant women who consumed foods high in carotenoids. CR levels were higher in pregnant women who consumed oranges/orange juice. ZL levels tended to be higher in pregnant women who consumed egg. TL levels did not differ by reported tomato intake. Pre-pregnancy body mass index (BMI) was negatively correlated with AC, BC, CR and TL levels. Whereas, BMI at time of sampling was negatively correlated with AC, BC and CR levels. The α-diversity (Chao1, Shannon) of the fecal bacterial communities was positively correlated with AC and BC. Fecal bacterial community composition tended to be associated with reported intake of carotenoid containing foods and with plasma levels of AC, BC and TL. Conclusions: Carotenoid intake is associated with microbiota diversity and composition. This may reflect an effect of high fiber or improved overall dietary quality, rather than a specific effect of carotenoids, on the microbiota. A larger study will be needed to determine if diets high in carotenoids influence the microbiota independently of diets high in other fruits or vegetables. Funding Sources: NIH CHEAR (2018-PF05), MSU internal funds (AgBioResearch and faculty start-up).